Soulspace : creating a home that is free of clutter, full of beauty, and inspired by you - Balbes, Xorin, 1957- (New World Library, 2011)
"Expertly designed and decorated homes don't necessarily feel like havens to their dwellers or reflect, inspire, and celebrate what is essential about their inhabitants. Lauded designer and architectural conservator Xorin Balbes created the eight-stage SoulSpace transformation process to help his clients do just that. Through the stages -- assess, release, cleanse, dream, discover, create, elevate, and celebrate -- readers explore not only the design of their living spaces but also their own interiors: the ways they think, feel, and sense. Through client stories, exercises, Q & As, and bountiful photos and illustrations, Balbes guides readers to decode clues to what they wish for, deny, and need to move forward. Empowered with this self-knowledge, they are free to declutter, refresh, and enhance their living spaces. Suitable for any budget and for one wall or one room, apartments or mansions, Balbes's wonderfully unique technique nurtures and transforms both souls and their spaces"--